Mastering system identification in 100 exercises - Schoukens, J. (Johan); Pintelon, R. (Rik); Rolain, Yves (Wiley, 2012)
"This book enables readers to understand system identification and linear system modeling through 100 practical exercises without requiring complex theoretical knowledge. The contents encompass state-of-the-art system identification methods, with both time and frequency domain system identification methods covered, including the pros and cons of each. Each chapter features MATLAB exercises, discussions of the exercises, accompanying MATLAB downloads, and larger projects that serve as potential assignments in this learn-by-doing resource"-- |c Provided by publisher.